Effect of calcium hydroxide on the bond strength of two bioactive cements and SEM evaluation of failure patterns - Centenaro, Carolina Fabiana; Santini, Manuela Favarin; Rosa, Ricardo Abreu da; Nascimento, Angela Longo do; Kuga, Milton Carlos [UNESP]; Pereira, Jefferson Ricardo; Reis So, Marcus Vinicius (Wiley-Blackwell, 2016)
The aim of this study was to assess the effect of calcium hydroxide on bond strength of two bioactive cements. One-mm thick longitudinal slabs of root dentin were obtained from freshly extracted human monorradicular teeth (n=60). Simulated root perforations (1mm in diameter) were prepared in radicular dentin. Thereafter, the specimens were randomly divided into two groups (n=30), according to the repair material: MTA (n=30) and Biodentine (BD) (n=30). Next, the specimens in each group were further randomly divided into 4 equal subgroups (n=15) according to the prior use of Ca(OH)2: MTA/Ca(OH)2 and BD/Ca(OH)2 groups: perforations were filled with calcium hydroxide [Ca(OH)2] and after 7 days, it was removed, and MTA and BD groups: calcium hydroxide dressing were not used. Push-out test was performed at a crosshead speed of 1mm/min. Bond strength values were compared statistically using Kruskal-Wallis test and Dunn's post-test at a significance level of 5%. The failure analysis was performed using a stereoscopic and classified as adhesive, cohesive and mixed. The push-out bond strength of MTA and BD was not affected by the prior use of Ca(OH)2 (p>0.05). BD yielded higher push-out bond strength values compared with those of MTA, regardless of the use of Ca(OH)2 (p<0.05). Mixed failures were predominant in all groups. Ca(OH)2 placement for perforations sealing does not alter the bond strength of MTA and BD to the root dentin. BD presented higher bond strength values than MTA. SCANNING 38:240-244, 2016. (c) 2015 Wiley Periodicals, Inc.
Keywords: biodentine; endodontics; dentin; MTA cement; bioactive cements